Considerations for stakeholder engagement and COVID‐19 related clinical trials' conduct in sub‐Saharan Africa. Issue 1 (15th August 2020) - Folayan, Morenike Oluwatoyin; Brown, Brandon; Haire, Bridget; Babalola, Chinedum Peace; Ndembi, Nicaise
ABSTRACT: The aim of this study is to determine how stakeholder engagement can be adapted for the conduct of COVID‐19‐related clinical trials in sub‐Saharan Africa. Nine essential stakeholder engagement practices were reviewed: formative research; stakeholder engagement plan; communications and issues management plan; protocol development; informed consent process; standard of prevention for vaccine research and standard of care for treatment research; policies on trial‐related physical, psychological, financial, and/or social harms; trial accrual, follow‐up, exit trial closure and results dissemination; and post‐trial access to trial products or procedures. The norms, values, and practices of collectivist societies in Sub‐Saharan Africa and the low research literacy pose challenges to the conduct of clinical trials. Civil‐society organizations, members of community advisory boards and ethics committees, young persons, COVID‐19 survivors, researchers, government, and the private sector are assets for the implementation and translation of COVID‐19 related clinical trials. Adapting ethics guidelines to the socio‐cultural context of the region can facilitate achieving the aim of stakeholder engagement.